The American Historical Review (JSTOR)
The American Historical Review (AHR) is the official publication of the American Historical Association (AHA). The AHA was founded in 1884 and chartered by Congress in 1889 to serve the interests of the entire discipline of history. Aligning with the AHA?s mission, the AHR has been the journal of record for the historical profession in the United States since 1895?the only journal that brings together scholarship from every major field of historical study. The AHR is unparalleled in its efforts to choose articles that are new in content and interpretation and that make a contribution to historical knowledge. The journal also publishes approximately one thousand book reviews per year, surveying and reporting the most important contemporary historical scholarship in the discipline.
Keywords: American Studies